Makna Ibu Nyai Bagi Santriwati di Pondok Pesantren Al-I’tishom Karawang - Nurhalimah, Juag; Utamidewi, Wahyu; Budhiarti, Tri Widya (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
The hectic problem of decreasing character education, especially student manners and decency and high juvenile delinquency in the world of formal education does not affect the existence of Islamic boarding schools as educational institutions that excel in the moral education of their students, with more and more people looking at Islamic boarding schools to educate children's character and morals. they. This certainly cannot be separated from the role of the teacher, caregiver or supervisor of the students. Mrs. Nyai is one of the figures who has a role in nurturing, educating and guiding Santri, especially female Santri. Departing from this phenomenon, this study aims to find out what the meaning of the figure of Mrs. Nyai is for Santriwati at the Al-I'tishom Karawang Islamic Boarding School. This research method uses a qualitative method with a phenomenological approach, because researchers are trying to find out the phenomenon of the meaning of Mrs. Nyai for Santriwati based on the experience and role of Mrs. Nyai in Islamic boarding schools. The theory used in this study is the theory of symbolic interaction and the data obtained by this research were generated through in-depth interviews, observation, and documentation. The results of this study indicate that Santriwati interprets the figure of Mrs. Nyai as a teacher as well as a parent at the Islamic Boarding School. Based on her communication experience, Santriwati interprets the figure of Mrs. Nyai as a person who is friendly, kind-hearted, has a high sense of sympathy, firm and wise. Keywords: Santriwati, Mrs. Nyai, Meaning, Islamic boarding school